Microbially enhanced dissolution of calcite in sinking marine particles - Benedict Borer; Adam V. Subhas; Matthew G. Hayden; Ryan J. Woosley; Andrew R. Babbin (Proceedings of the National Academy of Sciences, 2026)
Evidence for the shallow cycling of calcium carbonate in the global ocean is mounting, but the mechanisms driving the dissolution of thermodynamically stable polymorphs, like aragonite and calcite, in the surface ocean remain unconstrained. Here, we quantify how microbial metabolism creates acidic microenvironments in marine particles that enhance the local dissolution of calcite despite supersaturated conditions in bulk waters. A temporal decoupling of particle deoxygenation and acidification suggests that respiration-derived carbon dioxide is not the sole driver of the observed undersaturation. Rapid dissolution occurs in particles exhibiting bacterial growth, with rates exceeding abiotic dissolution at the same bulk saturation by more than an order of magnitude. We observe the highest particle-associated dissolution rates at intermediate settling velocities, indicating that a trade-off between elevated mass transfer due to settling and bacterial respiration governs the ensuing dissolution rates. Translation of our experiments to the water column suggests that microbially driven undersaturation in marine particles may dissolve sufficient calcite in the mesopelagic ocean to extend particle transit times by eliminating this vital ballast mineral, reducing the efficiency of organic carbon sequestration.